Knowledge and Challenges of Grade 11 Students in Learning Basic Business Math - Jacosalem, Hannah Mae; Futalan, Maria Chona (Journal of Interdisciplinary Perspectives, 2025)
The study aimed to identify students' perceived knowledge of Basic Business Math topics, the challenges they encountered, and the relationship between these factors. The researchers employed a descriptive-correlational design and utilized a stratified sampling technique. The respondents were 245 Grade 11 students. A validated questionnaire was used to collect data, which was analysed using mean, percentage, and Spearman’s rho. The results revealed that, in general, students perceived their knowledge of Basic Business Math as very satisfactory in the following topics: simple and compound interest, simple and general annuities, stocks and bonds, and business and consumer loans. However, approximately 10% of students rated their knowledge as only satisfactory. The study further indicated that students experienced moderate challenges related to basic knowledge, learning interest, lesson retention, and time allocation. On average, around 20% of students reported facing these challenges to a high or very high extent. Moreover, the data showed a significant relationship between students’ overall level of knowledge and the challenges related to basic knowledge and time allocation. Conversely, no significant relationship was found between students’ overall knowledge level and the challenges associated with learning interest and lesson retention.